Development of decentralized application (DApp) using blockchain technology to improve healthcare and medical record systems in Malaysia - Lim, Jason (2022)

(untitled)
Healthcare has always been substantial to a country and its economy. It signifies the strength and stability of a country, and without proper healthcare, the country will not be as efficient and successful. Hence, the medical record systems have to be remodified and improved for healthcare services to be efficient. In this project, blockchain technology and smart contracts will be the proposed method to solve issues with current medical record systems. Blockchain technology and smart contracts are nascent but rapidly growing technologies. These technologies can provide drastic improvements to solve key issues faced by almost every traditional medical record system. By utilizing blockchain to store medical records, we can leverage the benefits of blockchain, such as immutability, security, and decentralization. Next, smart contracts are the fundamental part of integrating any applications with the blockchain. It allows the automation of manual tasks that normally require manual labour, significantly reducing hospital labour costs. In this report, issues faced by traditional medical record systems are discussed, and each problem can be solved by implementing a blockchain medical record system. The developed system solves all of the key issues mentioned in the problem statement and achieves all of the objectives stated, proving that blockchain truly is the next big step forward in medical record systems.